2009
DOI: 10.1007/s10115-009-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

Integration of decision support systems to improve decision support performance

Abstract: Decision support system (DSS) is a well-established research and development area. Traditional isolated, stand-alone DSS has been recently facing new challenges. In order to improve the performance of DSS to meet the challenges, research has been actively carried out to develop integrated decision support systems (IDSS). This paper reviews the current research efforts with regard to the development of IDSS. The focus of the paper is on the integration aspect for IDSS through multiple perspectives, and the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 100 publications
(114 reference statements)
0
77
0
1
Order By: Relevance
“…This capability was enriched since PDSS-LEP supports model integration through the repeated generation of MR model and the use of another model which is PART. Model integration is the process whereby individually developed sub-models are logically combined to create a large unified model [16]. However, it was suggested that data integration should also be improved along with model integration by allowing multiple sources of data.…”
Section: Discussionmentioning
confidence: 99%
“…This capability was enriched since PDSS-LEP supports model integration through the repeated generation of MR model and the use of another model which is PART. Model integration is the process whereby individually developed sub-models are logically combined to create a large unified model [16]. However, it was suggested that data integration should also be improved along with model integration by allowing multiple sources of data.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of the knowledge management function into classic DSS can improve decision making performance in two senses: (1) enhancing the quality of services by having an "expert" readily available to users when human experts are in short supply [4]; (2) assisting a human expert by making their decisions more consistently [8]. Since 1990s, knowledge management has been playing an important role in the new generation of DSS known as KB-DSS.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, it is essential that decision makers seek-out knowledge through appropriate knowledge repository, reuse strategy and mechanisms. Furthermore, decision makers could benefit tremendously from easy to use knowledge systems that could equip them with extra expertise and knowledge about the decision problems and stimulate creative solutions to those problems [4]. To address the above issues, the concept of a new generation of DSS emerged in 1980s to include a knowledge management function and the systems were named as knowledge-based decision support systems (KB-DSS) [1], [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Integration is an important task in decision support process (Chiclana et al, 1998;Rao, 2008;Liu et al, 2010;Perçina and Kahramanb, 2010;Vu et al, 2014), as well as it does in group decision making process with preference information on alternatives (Cabrerizo et al, 2013;Chiclana et al, 2013). In group decision making process, multiple experts are always involved and express their preference information on alternatives in different formats due to different culture and education backgrounds, such as, fuzzy preference relations , pairwise comparison(Saaty, 2008, linguistics with different granularities (Mata, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%